Grid-tied Transformer-less Boost Switched Capacitor Topology (TLBSCT) for PV applications - Sidharth Samantara; A. Muruli Krishna; Kasinath Jena; Krishna Kumar Gupta; Dhananjay Kumar; Niraj Kumar Dewangan (PLoS ONE, 2026)
This paper proposes a new grid-tied transformer-less boost switched capacitor topology (TLBSCT) that employs three capacitors and twelve switches to generate seven levels with a gain of three times. The salient features of the TLBSCT are its boosting capacity, zero leakage current, minimum switching devices and lower voltage stress. The capacitors of the proposed TLBSCT have self-balancing characteristics. The proposed TLBSCT offers a brief discussion of the configuration, principle of working and the design of the parameter, as well as its control scheme. In addition, a comparative study of the proposal against the current transformerless inverter (TLI) shows the better performance of the proposed approach(PA). Also, the theoretical concept and viability of the suggested design have been demonstrated by simulations and experiments. This work contributes to SDG 7: Affordable and Clean Energy by improving efficient and reliable grid-connected solar power conversion systems.